Effect of impurity addition on the corrosion and carburization behavior of alloy 800HT in CO2 environment at 600 °C - Muthu Shanmugam Mannan; Gokul Obulan Subramanian; Taejeong An; Changheui Jang (Journal of Materials Research and Technology)
The corrosion and carburization behavior of Alloy 800HT was investigated in CO2, CO2+CH4, CO2+CO, and CO2+O2 environments at 600 °C (0.1 MPa) for 500 h. The addition of impurities resulted in reduction of oxidation but an increase in carbon activity. While O2 impurity addition significantly reduced the oxidation rate and the carbon activity due to the high p(O2). Transmission electron microscope and energy dispersive spectroscopy (TEM-EDS) results showed the development of thin Cr-rich and Mn/Cr spinel oxide layer and different shapes of Cr-rich M23C6 carbides in the matrix region. The CO addition showed a larger carburization region in the matrix. In all conditions, a Cr-depleted region appeared beneath the chromia oxide layer. In addition, the impurities promoted the development of Cr-rich precipitates in the Cr-depleted region, which is not observed in pure CO2.